Establishing occupational health & safety management system at the University of Tripoli according to the German universities - Albarouni, Mohamed Abdulhakim; shafighi, Najla (Archives of Business Research, 2021)
This study aims to examine the possibility of implementing and establishing the Occupational Health & Safety Management System (OHSMS) program that contributes significantly to improving the level of services provided by universities in Libya. This purpose relied on a quantitative and descriptive-analytical approach, which is based on describing the phenomenon and then providing explanations related to the implementation of OHSMS. Several statistical analysis tools were used to analyze the questionnaire in this paper using SPSS. The target respondents are students, faculty, and administration employees at the University of Tripoli in Libya. The results of the study revealed a set of results, the most important of which are: there is currently no effective system or effective measures for occupational health and safety at the university, as well as the absence of any health services at the university, as there is no private doctor at the university. The study also recommended the necessity of establishing a special department for occupational health and safety at the university as well as the necessity of paying attention to training university employees on occupational health and safety to enhance their awareness and the formation of specialized cadres in this field.